Combinatorial Approaches With Checkpoint Inhibitors to Enhance Anti-tumor Immunity - Seliger, Barbara (Frontiers in Immunology, 2019)
Treatment of tumor patients has been recently revolutionized by the application of various immunotherapeutics. However, the response rates are still limited ranging between approximately 20 and 40% suggesting that combinations of immunotherapy with conventional therapies, such as chemotherapy, radiotherapy as well as epigenetic modulators, targeted therapies using small molecules as well as other (immuno)therapeutics, might be an option to increase systemic anti-tumor immunity. It has been suggested that these non-immune based therapies in combination with immunotherapies could reprogram the immune suppressive tumor micromilieu and enhance the immunogenicity of tumor cells leading to an improved therapeutic efficacy and a better patients’ outcome. Despite there exist various examples of increased objective responses achieved by adding these different therapies to immunotherapies, strategies for rational and evidence-based design of checkpoint inhibitor combinations to maximize the clinical benefit for patients are urgently required. Therefore, this review will discuss (i) the major mechanisms of tumor cells to evade immune surveillance, (ii) strategies to revert these mechanisms and (iii) recent results from experimental models and clinical trials employed to enhance tumor immunogenicity by combining immunotherapy with different other therapeutic options to maximize patients’ outcome and minimize adverse events.